PENERAPAN MODEL PEMBELAJARAN PBL SEBAGAI UPAYA PENINGKATAN AKTIVITAS BELAJAR SISWA MATA PELAJARAN IPA KELAS IX-5 SMPN 1 NAMORAMBE - Darwin . (Universitas Negeri Medan, 2016)
Abstract: Application of PBL Learning Model as an Effort to Improve Student Learning Activities Subject Grade IX Ipa-5 SMPN 1 Namorambe. This study aims to look at the students' learning activities that include learning activities of students while working in groups in science subjects and also the results of student learning by applying the learning model Problem Based Learning. The research subject of class IX-5 SMPN 1 Namorambe totaling 28 people. Data activity of students in the first cycle read / write (41%), work (24%), asked fellow (8%), ask the teacher (14%), and are not relevant to KBM (13%). Data activity of students in the second cycle read / write (24%), work (50%), ask peers (19%), ask the teacher (2%), and are not relevant to KBM (6%). The results of student learning using learning model Problem Based Learning has increased. In the first cycle completeness of 60.7% with an average of 70.7 and the second cycle increased by 92.85% with an average of 85.7 shows the complete individual and class. Keywords: Problem Based Learning Model Learning, Learning Activities IPA, IPA Learning Outcomes. Abstrak: Penerapan Model Pembelajaran PBL sebagai Upaya Peningkatan Aktivitas Belajar Siswa Mata Pelajaran Ipa Kelas IX-5 SMPN 1 Namorambe. Penelitian ini bertujuan untuk melihat aktivitas belajar siswa yang mencakup aktivitas belajar siswa saat bekerja dalam kelompok pada mata pelajaran IPA dan juga hasil belajar siswa dengan menerapkan model pembelajaran Problem Based Learning. Subjek penelitian ini kelas IX-5 SMPN 1 Namorambe berjumlah 28 orang. Data aktivitas siswa pada siklus I membaca/menulis (41%), bekerja (24% ), bertanya sesama teman (8%), bertanya kepada guru (14%), dan yang tidak relevan dengan KBM (13%). Data aktivitas siswa pada siklus II membaca/menulis (24%), bekerja (50%), bertanya sesama teman (19%), bertanya kepada guru (2%), dan yang tidak relevan dengan KBM (6%). Hasil belajar siswa dengan menggunakan model pembelajaran Problem Based Learning mengalami peningkatan. Pada siklus I ketuntasan sebesar 60,7 % dengan rata-rata 70,7 dan pada siklus II mengalami peningkatan sebesar 92,85 % dengan rata-rata 85,7 menunjukkan tuntas secara individu dan kelas.Kata Kunci: Model Pembelajaran Problem Based Learning, Aktivitas Belajar IPA, Hasil Belajar IPA.